Perkembangan Wilayah Islam Pada Masa Pemerintahan Umar Bin Khattab - Desi Asmara Delima; Yusdiah Pertiwi; Ellya Roza (Departement of Mathematics Education, 2024)
This article aims to discuss the development of Islamic territory during the reign of Caliph Umar bin Khattab from 13 A.H. to 23 A.H. Caliph Umar bin Khattab was the second caliph after Abu Bakr. With a reign of approximately ten years, Caliph Umar bin Khattab had many achievements. The achievements include many fields, such as in the field of structuring state administration, the field of economy, security and public order, and the most important is in terms of expanding the territory of Islam to the outside of the Arabian Peninsula. This article is based on literature research using qualitative methods directed at content analysis. The results found are that the reign of Caliph Umar bin Khattab had a great influence on the development of Islam, both in the Arabian Peninsula and other regions such as Damascus, Ajnadin, Palestine, Egypt, Iraq, Persia, Syiri, and Nahawand. Through the policies implemented by Caliph Umar bin Khattab by dividing the territory into 8 provinces that oversee several districts and sub-districts. The eight provinces were Mecca, Medina, Syria, Jazirah, Kufa, Basra, Egypt and Palestine. For each of these districts, special officials were appointed as governors. Due to the expansion of the territory, the caliph Umar bin Khattab made several government administrative policies with several ministries that were needed according to the development of the country at that time. These important ministries include the Council al- Kharaj (tax ministry), Council al-Hadts (police ministry), He has also pioneered the ministry of public works (Nazarat al-Nafiah).